Post-ischemic treatment of WIB801C, standardized Cordyceps extract, reduces cerebral ischemic injury via inhibition of inflammatory cell migration. (20th June 2016) - Hwang, Sunyoung; Cho, Geum-Sil; Ryu, Sangwoo; Kim, Hoon J.; Song, Hwa Young; Yune, Tae Y.; Ju, Chung; Kim, Won-Ki
Abstract: Ethnopharmacological relevance: Anti-inflammatory therapy has been intensively investigated as a potential strategy for treatment of cerebral stroke. However, despite many positive outcomes reported in animal studies, anti-inflammatory treatments have not proven successful in humans as yet. Although immunomodulatory activity and safety of Cordyceps species (Chinese caterpillar fungi) have been proven in clinical trials and traditional Asian prescriptions for inflammatory diseases, its anti-ischemic effect remains elusive. Aim of the study: In the present study, therefore, we investigated the potential therapeutic efficacy of WIB801C, the standardized extract of Cordyceps militaris, for treatment of cerebral ischemic stroke. Materials and methods: The anti-chemotactic activity of WIB801C was assayed in cultured rat microglia/macrophages. Sprague-Dawley rats were subjected to ischemic stroke via either transient (1.5-h tMCAO and subsequent 24-h reperfusion) or permanent middle cerebral artery occlusion (pMCAO for 24-h without reperfusion). WIB801C was orally administered twice at 3- and 8-h (50 mg/kg each) after the onset of MCAO. Infarct volume, edema, blood brain barrier and white matter damages, neurological deficits, and long-term survival rates were investigated. The infiltration of inflammatory cells into ischemic lesions was assayed by immunostaining. Results: WIB801C significantly decreased migration of cultured microglia/macrophages. This anti-chemotactic activity of WIB-801C was not mediated via adenosine A3 receptors, although cordycepin, the major ingredient of WIB801C, is known as an adenosine receptor agonist. Post-ischemic treatment with WIB801C significantly reduced the infiltration of ED-1-and MPO-positive inflammatory cells into ischemic lesions in tMCAO rats. WIB801C-treated rats exhibited significantly decreased infarct volume and cerebral edema, less white matter and blood-brain barrier damages, and improved neurological deficits. WIB801C also improved survival rates over 34 days after ischemia onset. A significant reduction in infarct volume and neurobehavioral deficits by WIB801C was also observed in rats subjected to pMCAO. Conclusions: In summary, post-ischemic treatment of WIB801C reduced infiltration of inflammatory cells into ischemic lesions via inhibition of chemotaxis, which confers long-lasting histological and neurological protection in ischemic brain. WIB801C may be a promising anti-ischemic drug candidate with clinically relevant therapeutic time window and safety. Graphical abstract: